Perilaku Ibu dan Pemenuhan Gizi Pada Balita Usia 3-5 Tahun - Ratna Ningsih; Adella Winda Priana; Eviana S Tambunan; Yupi Supartini; Titi Sulastri (Jurnal Keperawatan, 2023)
Background: The problem of eating difficulties in toddlers is a common thing. Knowledge and attitudes that exist within a person are the main factors that can affect behavior. This includes the mother's method of feeding the child, regulating the atmosphere at mealtime, the variety of food provided by the mother and the type of food, the timing of feeding and the frequency of feeding the child. Mother's behavior if based on good knowledge will encourage mothers to provide optimal results in fulfilling nutrition for children. The purpose of this study was to see the relationship between the factors that affect the behavior of mothers in fulfilling nutrition for toddlers aged 3-5 years in Bahagia Village. Methods: This research used a quantitative design with observational analytics and a cross sectional approach. The population in this study were all mothers with toddlers in Bahagia Village with a total sample of 126 respondents. This study uses the Disproportionate Stratified Random Sampling technique and data analysis using the Chi-Square test. Results: The results of research conducted on 126 respondents, showed a significant relationship between mother's education, mother's knowledge, and family support with the p value of mother's education (p = 0.007), mother's knowledge (p = 0.008), and family support (p = 0.008) =0.000. Conclusion: Factors that significantly affect the mother's behavior in providing nutrition of children age 3-5 years are mother's education, mother's knowledge and family support.